The Socio-Economic Effects of Covid-19 Global Pandemic on Nigeria’s Development: Array - Orhero, Abraham Ejogba; Oghuvbu, Ejiroghene Augustine (Journal of Danubian Studies and Research, 2020)
This paper investigates the socio-economic effects of the COVID-19 pandemic on Nigeria’s development. The global Corona virus pandemic is the latest health disaster in the 21st century. The disease originated from the Wuhan province of China in December 2019 and has spread to numerous countries of the world including Nigeria. The study is anchored on the Linkage theory which helps to explain the implication of the pandemic on Nigeria’s security. The study employs the qualitative method, utilises the case study research design and relies on secondary data as drawn from books, book chapters, academic journals, newspapers and online sources. Findings of the study highlight that the pandemic has resulted in increase in unemployment, reduced revenues and increased crime rates. Consequently, the study recommends that palliatives measures should be adopted by the government to cushion the effects of the pandemic for organisations, businesses and individuals, especially the unemployed. In addition, government should intensify security measures to reduce and prevent crimes in Nigeria.